Advanced sensor and detection materials - Tiwari, Ashutosh; Demir, Mustafa M. (Salem, Massachusetts : Scrivener Publishing ; Hoboken, New Jersey : Wiley, 2014)
Authored by senior researchers for a large readership, this book presents an interdisciplinary review of the major cutting-edge technology research areas{OCLCbr#97}especially those on new materials and methods as well as advanced structures and properties{OCLCbr#97}for various sensor and detection devices. --
6.4 Humidity Sensing Materials6.5 Issues with Traditional Materials in Sensing Technology; 6.6 Introduction to Mesoporous Silica; 6.7 M41S Materials; 6.8 SBA Materials; 6.9 Structure of SBA-15; 6.10 Structure Directing Agents of SBA-15; 6.11 Factors Affecting Structural Properties and Morphology of SBA-15; 6.12 Modification of Mesoporous Silica; 6.13 Characterization Techniques for Mesoporous Materials; 6.14 Humidity Sensing of SBA-15; 6.15 Extended Family of Mesoporous Silica; 6.16 Other Applications of SBA-15; 6.17 Conclusion; References.
Includes bibliographical references and index.
Online resource; title from PDF title page (Wiley, viewed July 21, 2014).
Keywords: Detectors -- Materials; TECHNOLOGY & ENGINEERING -- Technical & Manufacturing Industries & Trades; Detectors -- Materials; Electronic books